Stay-At-Home Orders, Social Distancing and Trust - Abel Brodeur; Idaliya Grigoryeva; Lamis Kattan (Institute of Labor Economics (IZA), 2020)
Better understanding whether and how communities respond to government decisions is crucial for policy makers and health officials in response to the COVID-19 pandemic. In this study, we document the socioeconomic determinants of COVID-19 stay-at-home orders' compliance in the U.S. Using cell phone data measuring changes in average distance traveled and non-essential visitation, we find that: stay-at-home orders reduce mobility by about 8–10 percentage points; high-trust counties decrease their mobility significantly more than low-trust counties post-lockdown; and counties with relatively more self-declared democrats decrease significantly more their mobility. We also provide evidence that the estimated eeffct on compliance post-lockdown is especially large for trust in the press, and relatively smaller for trust in science, medicine or government.
Keywords: H12; I12; I18; 330; COVID-19; stay-at-home orders; social distancing; trust